Increased dietary protein for lactating sows affects body composition, blood metabolites and milk production. (1st August 2019) - Strathe, A. V.; Bruun, T. S.; Tauson, A.-H.; Theil, P. K.; Hansen, C. F.
Abstract : Hyper-prolific sows nurse more piglets than less productive sows, putting a high demand on the nutrient supply for milk production. In addition, the high production level can increase mobilization from body tissues. The effect of increased dietary protein (104, 113, 121, 129, 139 and 150 g standardized ileal digestible (SID ) CP/kg) on sow body composition, milk production and plasma metabolite concentrations was investigated from litter standardization (day 2) until weaning (day 24). Sow body composition was determined using the deuterium oxide dilution technique on days 3 and 24 postpartum . Blood samples were collected weekly, and milk samples were obtained on days 3, 10 and 17 of lactation. Litter average daily gain (ADG ) peaked at 135 g SID CP/kg ( P < 0.001). Sow BW and back fat loss reached a breakpoint at 143 and 127 g SID CP/kg ( P < 0.001). Milk fat increased linearly with increasing dietary SID CP ( P < 0.05), and milk lactose decreased until a breakpoint at 124 g SID CP/kg and 5.3% ( P < 0.001) on day 17. The concentration of milk protein on day 17 increased until a breakpoint at 136 g SID CP/kg (5.0%; P < 0.001). The loss of body protein from day 3 until weaning decreased with increased dietary SID CP until it reached a breakpoint at 128 g SID CP/kg ( P < 0.001). The body ash loss declined linearly with increasing dietary SID CP ( P < 0.01), and the change in body fat was unaffected by dietary treatment ( P =0.41). In early lactation (day 3 + day 10), plasma urea N (PUN ) increased linearly after the breakpoint at 139 g SID CP/kg at a concentration of 3.8 mmol/l, and in late lactation (day 17 + day 24), PUN increased linearly after a breakpoint at 133 g SID CP/kg ( P < 0.001) at a concentration of 4.5 mmol/l. In conclusion, the SID CP requirement for sows was estimated to 135 g/kg based on litter ADG, and this was supported by the breakpoints of other response variables within the interval 124 to 143 g/kg.